Japan's Multi-Track Diplomacy in Increasing Its Halal Tourism Branding - Damakhiroh, Wira; Sagena, Uni W. (LifeSciFi, 2024)
This study aims to examine and describe how Japan's Multi-Track Diplomacy enhances its Halal Tourism Branding, using the concepts of Multi-Track Diplomacy, Nation Branding, and Halal Tourism. The study employs a descriptive research method with library research data collection techniques, using secondary data from books, journals, and articles, analyzed qualitatively. The results show that out of the nine actors involved in Japan's Multi-Track Diplomacy to improve Halal Tourism Branding, six actors have been actively engaged. These include Government Institutions such as JNTO and JETRO, Instagram celebrities from Private Citizens, Muslim Communities in Japan, Business Actors, and the media as intermediaries, specifically Nippon Hoso Kyokai (NHK) World Japan. The findings indicate that various actors play crucial roles in promoting Japan's halal tourism and enhancing its branding image among the public.